The combination of platelet count and lymphocyte to monocyte ratio is a prognostic factor in patients with resected breast cancer - Deng, Yunfu (Medicine (Baltimore), 2020)
Many inflammation indicators have been reported to be related with patient outcomes in various cancers. Previous studies have evaluated the combination of platelet (PLT) and lymphocyte to monocyte ratio (COP-LMR) as a systemic inflammatory marker for prognostication in lung cancer, yet its prognostic role among breast cancer patients remains unclear. In the present study, a total of 409 breast cancer patients with surgical resection were retrospectively investigated. The receiver operating characteristic (ROC) curve was used to choose the optimal cut-off value of PLT and lymphocyte to monocyte ratio (LMR). Patients were classified into 3 groups according to the score of COP-LMR, and its relationship with various clinicopathological factors and breast cancer prognosis were further evaluated. The ROC curve analysis showed that COP-LMR had a higher area under the ROC curve for the prediction of 5-year disease-free survival and overall survival than PLT or LMR alone. Multivariable analysis showed that an elevated COP-LMR was an independent predictor of poor disease-free survival (P = .032) and overall survival (P = .005). Subgroup analysis revealed that COP-LMR was still significantly associated with prognosis in both luminal A and luminal B subtypes. Preoperative COP-LMR is a potential prognostic factor in breast cancer patients who underwent surgery.